Pengaruh Persepsi Manajer atas Informasi Akuntansi Keuangan terhadap Keberhasilan Perusahaan Kecil - Kiryanto Kiryanto; Dedi Rusdi; Sutapa Sutapa (The Indonesian Journal of Accounting Research, 2013)
The objective of this research is to find whether or not the internal factors such as learning process, motivation, and personality might influence againts the manager’s perception on the financial accounting information and to know whether the existing perception might influence againts the success of managing small bussines.This research is undertaken in the Small Business Environment Bugangan Semarang. The collection of data is done by providing questionaire to the collected manager’s and by interviewing  to complete the required data. The collected data will be processed by SPSS and be analyzed by regression analysis.The result of this analysis may show that learning process, motivation, and personality which become the intenal factors together have a positif influence againts the manager’s perception on financial accounting information. Furthermore, the result of this analysis may also show that the manager’s perseption on financial accounting information has a positif influence againts the success small bussines.